Evaluation of direct Etest for antimicrobial susceptibility testing of bacteria isolated from synovial fluid of horses using enrichment bottles. (February 2017) - Dumoulin, M.; Martens, A.; Van den Abeele, A.-M.; Boyen, F.; Oosterlinck, M.; Wilderjans, H.; Gasthuys, F.; Haesebrouck, F.; Pille, F.
Highlights: The Etest was able to be used for susceptibility testing in equine synovial infections. The Etest was performed directly on positive blood culture media (direct Etest). The direct Etest provided reliable susceptibility results for most antimicrobials. The direct Etest was more reliable than the conventional disk diffusion method. The direct Etest was less reliable than the standard Etest for determining minimum inhibitory concentration (MIC) values. Abstract: This study evaluated the Etest for direct antimicrobial susceptibility testing (AST) of bacteria from equine synovial specimens, incubated in BACTEC enrichment bottles. Ninety-four culture-positive broths were inoculated onto agar to directly determine the minimum inhibitory concentrations (MICs) of 13 antimicrobials, using the Etest (direct Etest). Results were compared with those obtained with the agar dilution reference method, the standard Etest, and the disc diffusion method, after subculture and standardisation of the inoculum. For categorical comparison of AST results, MICs were translated into susceptibility categories, using clinical breakpoints. The direct Etest predicted categorical susceptibility/resistance of bacteria from equine synovial fluid with acceptable accuracy (overall categorical agreement, 91%) and was more reliable than the disc diffusion test. The direct Etest was less accurate than the standard Etest for generating MICs ± 1 log dilution relative to the reference method (overall essential agreement, 69% vs. 89%). As the Etest generated a high percentage of inaccuracies with trimethoprim and sulfadiazine, these were less suitable antimicrobial agents for inclusion. In conclusion, the direct Etest reliably predicted the susceptibility of isolates from equine synovial fluid for the tested antimicrobials, except for trimethoprim and sulfadiazine. Since it did not require subculture and preparation of a standardised inoculum, direct Etest results were available at least 24 h earlier than with other methods, which could facilitate the diagnosis of synovial infections. However, when accuracy is prioritised over speed for MIC determination, the standard Etest is preferred over the direct Etest.